1976
DOI: 10.1128/aem.31.1.127-133.1976
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effect of dihydroxyphenyl compounds on the aerotolerance of Spirillum volutans and Campylobacter fetus subspecies jejuni

Abstract: The aerotolerance of the microaerophilic bacterium Spirillum volutans was greatly stimulated in a defined medium by the presence of dihydroxyphenyl ferric iron-binding compounds such as nor-epinephrine at 10-5 to 10-6 M. Dihydroxyphenyl compounds at 2 x 10-4 M, or iron salts (ferrous or ferric) at high concentration, greatly increased the aerotolerance of a strain of Campylobacter fetus subsp. jejuni when grown on streak plates of Brucella agar. The results suggest that the microaerophilism of these organisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…The details of the commercial production of tryptone undoubtedly vary from one manufacturer to another, and it is likely that factors such as temperature and conditions of desiccation may be responsible for the variability. For instance, if the processing were somehow to cause oxidation of some of the tyrosine in the tryptone to even micromolar amounts of dihydroxyphenyl compounds, this might profoundly influence oxygen tolerance (Bowdre et al 1976).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of the commercial production of tryptone undoubtedly vary from one manufacturer to another, and it is likely that factors such as temperature and conditions of desiccation may be responsible for the variability. For instance, if the processing were somehow to cause oxidation of some of the tyrosine in the tryptone to even micromolar amounts of dihydroxyphenyl compounds, this might profoundly influence oxygen tolerance (Bowdre et al 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxyl radical scabengers included allopurinol (Moorehouse et ui. 1987), azelaic acid (Passi et al 1991), caffeine (Shi et al 1991), carnosine (Pavlov et al 1991;Salim-Hanna et al 1991), cimetidine (Uchida and Kawakishi 1990), dimethylsulphoxide (DMSO ; Cederbaum et al 1977;Repine et al 1981), dimethyl thiourea (Repine et al 1981) and thiourea (Cederbaum et al 1979). The hydrogen peroxide scavengers were bovine liver catalase (Martin et al 1976) and sodium pyruvate (Thompson et al 1951).…”
Section: Reactive Oxygen Intermediate Scavengersmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing body of research indicating that the host microbiota, including commensals and pathogens, may respond to the presence of catecholamines. Norepinephrine has been shown to be a beneficial growth adjuvant to E. coli in serum-based media (Kinney et al, 2000) with a primary effect of enhancing iron acquisition (Bowdre et al, 1976;Freestone et al, 2000). Further tying together the virulence systems of E. coli O157, with an norepinephrine-influenced environment within the GI tract, it has been shown that norepinephrine enhances growth and iron acquisition, effects motility, increases toxin expression, and promotes attachment of E. coli O157 in vivo (Lyte et al, 1996aFreestone et al, 1999Freestone et al, , 2000Chen et al, 2003;Green et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Norepinephrine and epinephrine induce 158 and 105 genes, respectively, of which only 18 are common to both catecholamines, in the porcine respiratory pathogen Actinobacillus pleuropneumoniae (Li et al, 2012). Norepinephrine can change Campylobacter jejuni, a foodborne pathogen, from a microaerotolerant to an aerotolerant organism (Bowdre et al, 1976). As stress is an everyday factor for swine from birth until slaughter, so is the constant bi-directional communication between swine host and microbiota.…”
Section: Introductionmentioning
confidence: 99%